Towards an Interdisciplinary Diagnostic of the Expansion of the Criminal and Prison Universe in Costa Rica: 1990-2022 - Baraona Cockerell, Miguel (2021)
This article presents the empirical and theoretical basis, as well as the practical methodological strategy (concrete steps for the implementation of the conceptual framework), in line with the interdisciplinary and intergnosis perspectives that we present here. This work expands on the main ideas in the second point, by providing an empirical description of the problem examined by this research, and thus advancing a glimpse into the complexity of the two intertwined phenomena (criminal universe and prison universe) and the failure of criminalistic and/or sociological theories concerning the causes and genesis of criminal behavior as well as the policies and measures derived from them in order to prevent, contain, and reduce it in the final analysis. The two following points, examine the main conceptual aspects that guide and define the particular nature of this project, as well the chronological planning of its practical implementation from the year 2021 until the year 2023, and also the definition of the socio-institutional sectors to whom the products of this work will be destined. Having been one of the projects awarded funding by the Fund for Research and Academic Development (FRAD) of the National University of Costa Rica, its future viability and implementation are firmly guaranteed for the two academic years from January 2021 to January 2023. During the third and last year of the project, we shall finish editing and polishing the two main products of this research, which are the collective book and an Executive Report on the topics under study; the latter product will be eventually presented at the National Assembly of Costa Rica.